Effects of crystal planes on topography evolution of silicon surface during nanoscratch-induced selective etching. (15th March 2021) - Wu, Lei; Chen, Peng; Deng, Liang; Zhang, Pei; Yu, Bingjun; Qian, Linmao
Abstract: Diamond machining-induced structural defects can usually degrade the optical and electrical performance of silicon (Si)-based devices. Investigating topography evolution of machined Si surfaces during wet etching is of significance for detecting and eliminating these defects and thereby improving device performance. In this paper, effects of Si crystal planes on surface topography evolution during nanoscratch-induced selective etching in the commonly used etchants, i.e., potassium hydroxide (KOH), tetra-methyl-ammonium hydroxide (TMAH), and a mixture of hydrofluoric acid (HF) and nitric acid (HNO3 ), were investigated using a single-asperity diamond tip. It is noted that nanoscratch-induced subsurface deformation of Si(100) and Si(110) can resist KOH and TMAH solutions etching, and thereby in situ form protrusive hillocks, which can be ascribed to the amorphous Si from the scratching. Higher etching rate of Si(110) planes appears to be responsible for the formation of higher protrusive hillocks. Nevertheless, nanoscratch-induced selective etching on Si(111) surface in TMAH solution is quite distinct from that in KOH solution. The difference in activated atomic steps on Si(111) surface may cause scratched regions to promote KOH etching but resist TMAH etching. It is also found that in case of HF/HNO3 mixtures etching, nanoscratch-induced subsurface deformation on Si surface can promote the etching and thereby form sunken grooves, regardless of crystal plane orientations. Further analysis indicates that Si wafers with lower hardness and elastic modulus are beneficial for forming more serious subsurface damages during the scratching, yielding deeper sunken grooves through subsequent selective etching. These findings provide a useful reference for defect detection on Si surface and developing the nanofabrication based on scanning probe microscope.